The Patella : Anatomy, Variations and Clinical Relevance - Saputra, Andi (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2025)
The patella, or kneecap, is the largest sesamoid bone in the human body and plays a crucial role in knee biomechanics. This review provides a comprehensive overview of the anatomy, structural variations, and clinical significance of the patella. We examine its macroscopic and microscopic structure, variations such as bipartite patella, and their implications in clinical practice. Additionally, the review highlights the patella's biomechanical contributions, its role in common pathologies, and its importance in surgical and rehabilitation contexts. Understanding the patella's anatomy and variations is essential for improving diagnosis, treatment, and patient outcomes in knee-related conditions.